(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2019)
Background : Breast cancer remains a leading dreadful cancer of women in Bangladesh. Lack of screening program is the reason behind this high morbidity and mortality. The Government of Bangladesh (GOB) has taken initiative to develop a breast cancer screening program by Clinical Breast Examination (CBE) throughout the country. But there is almost no information on baseline prevalence of breast cancer in Bangladesh. Moreover, cancer surveillance is a fundamental element of the Cancer Control Strategy. To form a foundation of this surveillance program, the survey was done to determine the breast cancer prevalence in Chittagong Division of Bangladesh. Materials and methods: This cross-sectional population-based survey was conducted by the department of Surgery, Chattogram Medical College Hospital, in Chattogram Division from 01.12.2017 to 31.04.2018. Females willing to participate in the survey were included from 4 Upazilas (Anwara, Boalkhali, Lohagara and Patiya) of Chattogram district. CBE of the study population was performed by trained physicians to identify the suspected positive physical signs for breast carcinoma. These patients were further investigated by FNAC. Data were collected and analyzed. Results: Out of 732 women surveyed, 2 subjects (A crude prevalence rate of 273.22/100,000 women) were finally diagnosed as carcinoma breast and another 29 had benign breast disease. Conclusions: This survey is an initiative towards a large scale itra-divisional epidemiological investigation inBangladesh. The peak of breast cancer incidence in Bangladesh may be 15–20 years before the peak incidence in Western countries, suggesting that more attention should be paid to the premenopausal women. JCMCTA 2018 ; 29 (2) : 4-8